Two-photon polymerisation 3D printed freeform micro-optics for optical coherence tomography fibre probes. Issue 1 (December 2018) - Li, Jiawen; Fejes, Peter; Lorenser, Dirk; Quirk, Bryden; Noble, Peter; Kirk, Rodney; Orth, Antony; Wood, Fiona; Gibson, Brant; Sampson, David; McLaughlin, Robert
Abstract Miniaturised optical coherence tomography (OCT) fibre-optic probes have enabled high-resolution cross-sectional imaging deep within the body. However, existing OCT fibre-optic probe fabrication methods cannot generate miniaturised freeform optics, which limits our ability to fabricate probes with both complex optical function and dimensions comparable to the optical fibre diameter. Recently, major advances in two-photon direct laser writing have enabled 3D printing of arbitrary three-dimensional micro/nanostructures with a surface roughness acceptable for optical applications. Here, we demonstrate the feasibility of 3D printing of OCT probes. We evaluate the capability of this method based on a series of characterisation experiments. We report fabrication of a micro-optic containing an off-axis paraboloidal total internal reflecting surface, its integration as part of a common-path OCT probe, and demonstrate proof-of-principle imaging of biological samples.